Expression of DCX and Transcription Factor Profiling in Photothrombosis-Induced Focal Ischemia in Mice - Lv, Zhu-Man; Zhao, Rong-Jian; Zhi, Xiao-Song; Huang, Ying; Chen, Jia-Yin; Song, Ning-Ning; Su, Chang-Jun; Ding, Yu-Qiang (Frontiers in Cellular Neuroscience, 2018)
Adult neurogenesis is present in the dentate gyrus and the subventricular zone in mammalian brain under physiological conditions. Recently, adult neurogenesis has also been reported in other brain regions after brain injury. In this study, we established a focal striatal ischemic model in adult mice via photothrombosis and investigated how focal ischemia elicits neurogenesis in the striatum. We found that astrocytes and microglia increased in early post-ischemic stage, followed by a one-week late-onset of doublecortin (DCX) expression in the striatum. The number of DCX-positive neurons reached the peak level at day 7, but they were still observed at day 28 post ischemia. Moreover, Rbp-J (a key effector of Notch signaling) deletion in astrocytes has been reported to promote the neuron regeneration after brain ischemia, and we provided the change of gene expression profile in the striatum of astrocyte-specific Rbp-J knockout mice (GFAP-CreER:Rbp-Jfl/fl), which may help to clarify detailed potential mechanisms for the post-ischemic neurogenesis in the striatum.